2011
DOI: 10.1016/j.neuroimage.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence of disseminated subpial T2* signal changes in multiple sclerosis at 7 T: A surface-based analysis

Abstract: Cortical subpial demyelination is frequent in multiple sclerosis (MS) and is closely associated with disease progression and poor neurological outcome. Although cortical lesions have been difficult to detect using conventional MRI, preliminary data using T2*-weighted imaging at ultra-high field 7T MRI showed improved sensitivity for detecting and categorizing different histological types of cortical MS lesions. In this study we combined high-resolution 7T MRI with a surface-based analysis technique to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 45 publications
4
55
1
2
Order By: Relevance
“…High probability of focal grey matter demyelination was observed in the hippocampus, deep grey matter and insula 48,49 , whereas a significant increase in the distribution of diffuse subpial demyelination was observed by means of 7T magnetic resonance in the anterior cingulate cortex 50 .…”
Section: Evidence For Independent Grey Matter Damagementioning
confidence: 89%
“…High probability of focal grey matter demyelination was observed in the hippocampus, deep grey matter and insula 48,49 , whereas a significant increase in the distribution of diffuse subpial demyelination was observed by means of 7T magnetic resonance in the anterior cingulate cortex 50 .…”
Section: Evidence For Independent Grey Matter Damagementioning
confidence: 89%
“…Additionally, our global cortical and WM MRI metric analysis may be most sensitive to globally distributed cognitive domains, while being insensitive to regionally driven cognitive processes. An automated surface-based approach with both global and regional analyses of T2* signal change in the cortex may prove to be a more objective MRI metric at 7T to quantify intracortical pathology for future study of cognitive dysfunction in MS. 38 Our preliminary data identify CL metrics that are significantly associated with neurologic disability (primarily type III-IV CLs) and cognitive performance in MS-particularly the subpial (type III-IV) and leukocortical (type I) CLs that have not been associated previously in vivo. Moreover, we were able to determine these correlations with a small group of patients with MS. Because cognitive impairment in MS increases as the disease ensues, with or without similar levels of physical disability progression, further longitudinal observation of this cohort should allow us to identify global and regional mechanisms of injury responsible for both physical and cognitive disease progression.…”
mentioning
confidence: 79%
“…Because few patients had relatively high EDSS scores, spinal cord pathologic assessment is expected to have minimal influence on the correlations between EDSS and our cortical OEF measurements. In addition, pathologic data 35 and in vivo data 36,37 showed that cortical pathologic assessment, i.e., lesions and diffuse cortical damage, is also linked to higher EDSS. Cortical pathologic assessment, potentially including OEF changes, thus contributes to neurologic disability in MS in addition to spinal cord damage.…”
Section: Physiologic Interpretation Of Findingsmentioning
confidence: 99%
“…Furthermore, our LC analyses were based only on focal cortical lesions and did not consider subpial demyelination, which tends to involve larger cortical surfaces. 38 Surface-based techniques for assessing diffuse cortical changes 36 may provide more sensitive measures to investigate the relationship between cortical lesions and oxygen dysfunction in MS.…”
Section: Physiologic Interpretation Of Findingsmentioning
confidence: 99%